Rural Marketing: The New Paradigm - Ranjan, Rajeev Kumar (Prabandhan: Indian Journal of Management, 2010)
With more than 700 million people living in rural areas, in some 5, 80,000 villages, and with about two- thirds of its workforce engaged in agriculture and allied activities with a contribution of 29 percent to India's Gross Domestic Product (GDP), India's economy is predominantly rural in character. Increase in competition, saturated urban markets, new product demanding urban customers have made the companies think about new potential rural markets. Thus, Indian rural markets have caught the attention of many companies, advertisers and multinational companies. According to a recent survey conducted by the National Council for Applied Economic Research (NCAER), the purchasing power of the rural people has increased due to increase in productivity and better price commanded by the agricultural products. In economics, this rural market is termed as the bottom of the pyramid and it is the largest, but poorest socio-economic group. By and large, the rise in purchasing power of rural people remains unexploited and with the growing reach of the television, it is now quite easy for the marketers to capture these markets. Rural marketing has become the latest mantra of most of the corporates.Companies like Hindustan Lever, Colgate Palmolive, Britannia and even Multinational Companies (MNCs) like Pepsi, Coca Cola, L.G., Philips, and Cavin Kare are all eyeing rural markets to capture the large Indian rural market. The article attempts to provide insights into the Indian Bottom of the Pyramid market segment and the potential it could offer to a multinational company to expand its market and build a global base here. The Indian economy is growing at an annual rate of 8 percent. This growth is considerable when compared to the growth of European countries, which is less than 2 percent on a 10-year average, and the growth of the American economy, which is approximately 3 percent. Moreover, there has been significant reduction in poverty levels and increase in quality consciousness among the Indian rural and urban consumers who were 'under-served' in the past 10 years. This changing scenario in the Indian economy could translate into an investment opportunity for many multinational companies. The NCAER analysis shows an increase of over 150 percent in the number of consumer class households in the last 10 years. This emergence of the BOP segment could be defined as a new consumer market. The BOP market in India comprises of a population of 750 million (70 percent of the population) living in 600,000 villages (rural area).